Examining perceptions of a communication course for parents of children with profound intellectual and multiple disabilities. (16th March 2022) - Rensfeldt Flink, Anna; Åsberg Johnels, Jakob; Broberg, Malin; Thunberg, Gunilla
Abstract : The overall aim was to examine participants' perceptions of a communication course as held for parents of children with profound intellectual and multiple disabilities. The course curriculum included responsive strategies and augmentative and alternative communication. The research questions addressed the favourability, changes in parents' or children's communication and appreciated or unappreciated course features. Twenty-two written course evaluations were analysed. The mean scores for ratings were compared with ratings in a previous study, including those of parents of children with generally milder disabilities. Comments and answers to open-ended questions were analysed using thematic analysis. Participants were slightly more satisfied with the course as compared with parents who had children with milder disabilities. The thematic analysis suggested increased parental responsiveness after the course. Perceptions of augmentative and alternative communication varied. It was unclear whether the course altered the children's communication or not. The supportive social milieu offered by the course was highly appreciated. Although generalisation beyond this course and setting is to be determined, the results suggest that parents of children with profound intellectual and multiple disabilities can appreciate a communication course and find it useful. An individual approach within the group setting and practical learning opportunities seem important.